Answers

2014-11-25T16:37:41+05:30
x² - 7x + 12 = 0  

By factorizing method.

x² - 3x - 4x + 12  = 0

x(x- 3) - 4 ( x - 3) = 0
( x - 4 )( x - 3 ) = 0

x = 4   , x = 3

=========================================================
By second method
x² - 7x + 12 = 0

By quadratic formula

x = -b + √ b² - 4ac  ,    x = - b - √ b² - 4ac
             2a                                2a

x = 7 + √ 49 - 48    ,     x = 7 - √ 49 - 48
            2                                 2

= 8/2                ,       x = 6/2

x = 4                    ,        x = 3.
0